Quantifying the prevalence and adaptiveness of behavioral rationalizations. (2020) - Tierney, Warren; Uhlmann, Eric Luis
Abstract: Critical aspects of the "rationality of rationalizations" thesis are open empirical questions. These include the frequency with which past behavior determines attitudes (as opposed to attitudes causing future behaviors), the extent to which post hoc justifications take on a life of their own and shape future actions, and whether rationalizers experience benefits in well-being, social influence, performance, or other desirable outcomes.